Detection of somaclonal variants in somatic embryogenesis-regenerated plants of Vitis vinifera by flow cytometry and microsatellite markers - Prado, María Jesús (2020)
Flow cytometry and microsatellite analyses were used to evaluate the trueness-to-type of somatic embryogenesis-regenerated plants from six important Spanish grapevine (Vitis vinifera L.) cultivars. Tetraploid plants were regenerated through somatic embryogenesis from all of the cultivars tested with the exception of ‘Merenzao’.Inaddition,anoctoploidplantwasobtainedinthecv. ‘Albariño’, and two mixoploids in ‘Torrontés’. The most probable origin of these ploidy variations is somaclonal variation. The cv. ‘Brancellao’ presented signiﬁcantly more polyploids (28.57%) than any other cultivar, but it must be noted that 50% of the adult ﬁeld-grown ‘Brancellao’ mother plants analysed were mixoploid. Hence, it is probable that these polyploids originatedeither fromsomaclonal variation or by separation of genotypically different cell layers through somatic embryogenesis. Microsatellite analysis of somatic embryogenesis-regenerated plants showed true-totype varietal genotypes for all plants except six ‘Torrontés’ plants, which showed a mutant allele (231) instead of the normalone(237)atthelocusVVMD5.Therewasnotaclear relationship between the occurrence of the observed mutant regenerated plants and the callus induction media composition, the developmental stage of the inﬂorescences, the type of explant used for starting the cultures or the type of germination (precocious in differentiation medium ornormal in germination medium) in any of the cultivars tested, except ‘Torrontés’. The mutant plants described herein have been transplanted to soil for future evaluation of putative phenotypic traits of interest. These mutants can be useful both for breeding programs and for functional genomic approaches aimed at increasing knowledge of the biology of grapevine.